The development of an education provision model to enhance professional competencies of graduates in the workforce shortage fields of study - Howattanakul, Sutida (2010)
The purpose of this research is to develop professional competency model in the field of goldsmith and jewelry education and food industry and service education. The model was developed with the learning process of the national education act 1999 and the higher education commission 15 year plan in lifting up higher education quality standard, producing higher workforce, emphasizing on international competition, building network among institutions and certifying qualification in vocational area with border countries. The competency ideas offered to the research are from Mc.CLElland theory and UNESCO in career and vocational qualification competency.For research design, population are of the five goldsmith and jewelry institutions and five food and service industry institutions in the interview with the experts, the specialists, the employers and the institution administrators. Only the open-ended questionnaire technique was used for the instructors.After the interviews, data was analyzed by the content analysis, mean, S.D. and F-Test. Summary of research is that competency of the graduates should come from industry standard. The experience study from the industry has made specialized skill for the student. Institution and industry should corporate each other with qualification in curriculum planning and assessment. Industry should be part of field experience and institutional curriculum by being committee to define the skill standard, and for providing the standard set-up for solidification of the improved system of national qualification and quality assurance process as the stake holders’ responsiveness. The collected data shows the key competency, were the experience in working, the insight attitude, trait, and knowledge. The highly skill in verbal representing English communication is very important as well as computer skill. For the instructors, their strategies are knowledgeable in the original style of jewelry, searching for the new knowledge enthusiastically and emphasizing in self-evaluation with result-based theory. The instruction should find the needs of the stakeholders. They using transferable to each other by co-operating learning between industry and institution. The completing model complies with moral attitude in working, love, and honesty for self-sustain and organization. The contest and exhibition to present the work piece to enter the professional world with interpersonal relationship and the technological applied for generation the new knowledge.